Epidemiological profile and performance of triage decision-making process of COVID-19 suspected cases in southern Tunisia - Maissa Ben Jmaa; Houda Ben Ayed; Mondher Kassis; Mariem Ben Hmida; Maroua Trigui; Hanen Maamri; Nouha Ketata; Sourour Yaich; Jihene Trabelsi; Yosra Mejdoub; Manel Turki; Chakib Marrakchi; et al. (African Journal of Emergency Medicine, 2022)
Introduction: During an epidemic, screening processes can play a crucial role in limiting the spread of the infection. The aim of this study was to describe the epidemiological profile of COVID-19 suspected cases and to evaluate the performance of the triage process in predicting COVID-19 in Southern Tunisia. Methods: It was a prospective study including all patients consulting to the Hedi Chaker University Hospital departments from March to June 2020. A clinical triage score (CTS) was used to assess the risk of the infection and to refer patients to the appropriate part of the facility accordingly. Results: Overall, 862 patients were enrolled, among whom 505 patients (58.6%) were classified as suspected cases (CTS ≥4). Of these, 46.9% (n = 237) were of mild form. Samples were collected from 215 patients (24.9%), among whom five were COVID-19 positive, representing a positive rate of 2.3%. The in-hospital cumulative incidence rate of COVID-19 was 580/100000 patients. The total daily incidence decreased significantly during the study period (p < 0.001, chi-square for linear trend = 25.6). At a cut-off of four, the CTS had a sensitivity of 40%, a specificity of 32.4%, and negative and positive predictive values of 95.8% and 1.4%, respectively. Discussion: Although the triage process based on the CTS was not as performant as the RT-PCR, it was crucial to interrupt virus spread among hospitalized patients in “COVID-19-free departments”.